EPCO-33. DIFFERENTIAL EXPRESSION OF AN ENDOGENOUS RETROVIRAL ELEMENT [HERV-K(HML-6)] IS ASSOCIATED WITH REDUCED SURVIVAL IN GLIOBLASTOMA PATIENTS. (14th November 2022) - Shah, Ashish; Govindarajan, Vaidya; Doucet-O'Hare, Tara; Rivas, Sarah; Ampie, Leo; DeMarino, Catherine; Banasavadi-Siddegowda, Yeshavanath; Zhang, Yong; Johnson, Kory; Almsned, Fahad; Gilbert, Mark; Heiss, John; et al.
Abstract: INTRODUCTION: Comprising approximately 8% of our genome, Human Endogenous RetroViruses (HERVs) represent a class of germline retroviral infections that are regulated through epigenetic modifications. In cancer cells, which often have epigenetic dysregulation, HERVs have been implicated as potential oncogenic drivers. However, their role in gliomas is not known.Given the link between HERV expression in cancer cell lines and the distinct epigenetic dysregulation in gliomas, we utilized a tailored bioinformatic pipeline to characterize and validate the glioma retrotranscriptome and correlate HERV expression with locus-specific epigenetic modifications.Method:A custom workflow was used to quantify HERV expression in our cell lines of interest. Cell-line methylation was quantified using a custom script. We generated primers specific for the Human endogenous Mouse mammary tumor (MMTV)-Like virus 6 ( HML-6 ). Visualization of RNA transcripts was performed using RNA-scope. Clinical data was obtained using the R package, TCGABiolinks. RESULTS: The A172 cell line had significantly higher mean overall HERV expression relative to the M059J and H4 cell lines (p< 0.0001 for both). A172 cells had significantly lower mean number of CpG islands relative to M059J cells and H4 cells (p< 0.0001 for both). There was a significant inverse correlation between mean beta value and FC HERV expression (R=-0.57, p=0.01). qPCR confirmed robust expression of the HML-6 locus in cell culture and neurospheres. Elevated ERVK3-1 expression was associated reduced survival among IDHwt GBM patients (18.3 vs. 15.1 months, p=0.039). This was preserved among IDH mutant (IDHm) GBM as well (17.9 months vs. 14.0 months, p=0.0088). CONCLUSION: In gliomas, HERV expression correlates with loss of DNA methylation at HERV loci. HML-6 is overexpressed in highly invasive glioblastoma cell lines and patient-derived neurospheres. We have demonstrated a potential survival detriment associated with elevated expression of the HML-6 product, ERVK3-1.